Development of Teaching – Aid Materials for Teaching and Learning Biology: A Waste to Wealth Approach (Paper Mache) - Bolajoko, Atotileto Zainab; Adebayo, Bello Zakariyau (FKIP - Universitas Riau, 2023)
The campus today is littered with varieties of waste materials, which were generated from students' activities. The bulk of these wastes were solid wastes, and it is obvious that papers form a larger percentage of the waste on our campuses. These papers could include leftovers from students marked test scripts, detached textbook materials, personal notebooks, and jotters. Environmentalists have listed improper dumping of refuse and sewage disposal contamination as one of the major factors that hinder an eco-friendly society, most importantly in schools. One of the greatest problems confronting the education sector today is the lack of adequate instructional materials to teach the students. The cost of purchasing foreign-made instructional materials is on the high side. Hence, there has been serious agitation by educational technologists to venture into improvisation as alternatives to real objects. Using campus waste paper to mould improvised teaching aids for the teaching and learning of basic biological concepts will not only be of benefit to educators but also to environmentalists who are concerned about proper waste management. Up-cycling methodology was adopted for this study, which is the process of reusing waste materials without breaking them down into their base state to create another product.